WEIGHT REDISTRIBUTION ON SIMPLY CONNECTED GRAPHS WITH SYMMETRIC SCHEME - Rodiah, Isti
This thesis is an investigation of linear and iterative weight redistribution on sim- ply connected graphs. Averaging is one special case of redistribution. Linear local averaging is related to the discrete Laplace operator on graphs. The convergence criteria of the scheme is dened by spectral properties of the linear map. We develop successive symmetric local averaging scheme to ensure the monotony of iteration. In the end we show that the only redistribution possible on simply connected graphs is the averaging.